Proteinaceous Effector Discovery and Characterization in Plant Pathogenic Colletotrichum Fungi - Lu, Xinyu; Miao, Jinlu; Shen, Danyu; Dou, Daolong (Frontiers in Microbiology, 2022)
Anthracnose caused by plant pathogenic Colletotrichum fungi results in large economic losses in field crop production worldwide. To aid the establishment of plant host infection, Colletotrichum pathogens secrete numerous effector proteins either in apoplastic space or inside of host cells for effective colonization. Understanding these effector repertoires is critical for developing new strategies for resistance breeding and disease management. With the advance of genomics and bioinformatics tools, a large repertoire of putative effectors has been identified in Colletotrichum genomes, and the biological functions and molecular mechanisms of some studied effectors have been summarized. Here, we review recent advances in genomic identification, understanding of evolutional characteristics, transcriptional profiling, and functional characterization of Colletotrichum effectors. We also offer a perspective on future research.